James and the giant peach : a children's story - Dahl, Roald, 1916-1990.; Smith, Lane (New York : Puffin, 1996)
Wonderful adventures abound after James escapes from his fearsome aunts by rolling away inside a giant peach.
Book Links (A.L.A.).
Horn Book Starred.
Wilson's Children.
5.6.
5.6
3-6
Keywords: Aunts -- Fiction; Fairy tales; Fantasy; Insects -- Fiction; Peach -- Fiction; Aunts -- Fiction; Fairy tales; Insects -- Fiction; Peaches -- Fiction; Fantastic fiction